Taking Stock of Wholesale Power Markets in Developing Countries : A Literature Review - Rudnick, Hugh; Velasquez, Constantin (World Bank, Washington, DC, 2018)
Although many developing countries have yet to meet the considerable prerequisites for establishing wholesale power markets, a significant minority of larger middle-income countries have introduced diverse markets in the past 25 years. Cost-based pools proved particularly popular in Latin America and look to be a more straightforward starting point than the bid-based pools adopted in some other jurisdictions. Successful design of power markets involves paying careful attention to four guiding principles. First, trading arrangements must ensure efficient and reliable operation of the market, efficiently employing available resources not only to balance aggregate supply and demand, but also to allow congestion management and supply ancillary services. Second, market design should ensure strong participation of the demand side of the market, by allowing large customers to participate directly in the market, and medium ones to see spot market prices through time-of-use tariffs. Third, open access to the power grid should be guaranteed through industry restructuring, removal of barriers to entry of different players, and establishment of a neutral system operator. Fourth, a workable framework for supply adequacy is required to ensure capacity meets demand without imposing supply constraints. This may entail complementing efficient energy price signals with other mechanisms (such as auctions and capacity obligations) to provide adequate incentives for investment in new generation capacity. Experience demonstrates that the early stages of establishing power markets can be challenging and necessitate the creation of regulatory mechanisms for market monitoring that can identify and address emerging design flaws, particularly for abuses of market power. Countries not yet ready to introduce wholesale power markets may still benefit from several emerging regional power markets. Looking ahead, the design of power markets is becoming increasingly complex due to the challenges posed by disruptive technologies such as variable renewable energy, large-scale storage, and increasingly sophisticated demand-side participation.